Training a support vector machine in R with mlr, (Manning Publications, 2020)
Hefin I. Rhys teaches you how to train, tune, and cross-validate a Support Vector Machine model using RStudio and the awesome mlr machine learning package. He's the author of "Machine Learning with R, the tidyverse, and mlr".